Pedagogical Konten Knowledge dalam Numerasi: Studi pada Calon Guru Sekolah Dasar - Amelia Amri, Mira; Citra Aprilia, Anggi; Aruwiyantoko, Anggit (IJPSE Indonesian Journal of Primary Science Education, 2025)
Numeracy skills are essential competencies that students must possess to face the challenges of 21st-century life. Numeracy encompasses not only the ability to perform calculations but also includes conceptual understanding, application in real-life contexts, and data-driven decision-making. This article aims to explore in depth the Pedagogical Content Knowledge (PCK) of prospective elementary school teachers in solving numeracy problems. The study seeks to examine the PCK of prospective elementary school teachers in the context of numeracy, focusing on cognitive analysis and decision-making in mathematical problem-solving. Using a qualitative exploratory approach, data were collected through numeracy tests and interviews with students enrolled in an elementary teacher education program (PGSD). The findings reveal that the PCK of prospective elementary school teachers in numeracy consists of four main components: content knowledge, knowledge of students, knowledge of instructional strategies, and contextual knowledge. Specifically, it was found that the prospective teachers have a solid understanding of basic numeracy concepts but face challenges in applying effective strategies to address student errors. The study recommends further development in teacher training, particularly in decision-making and the adaptation of instructional strategies to suit students’ characteristics.